Leveraging network pharmacology for drug discovery: Integrative approaches and emerging insights - Lu Li; Supratik Kar (Medicine in Drug Discovery)
Network pharmacology (NP) is an interdisciplinary approach that integrates systems biology, omics technologies, and computational methods to identify and analyze multi-target drug interactions, validate therapeutic mechanisms, and advance the field of integrative drug discovery. This study explores the role of NP in drug discovery, emphasizing its capacity to identify drug-target-disease interactions, support drug repurposing, and integrate traditional and modern pharmacology. A comprehensive review was conducted, integrating systems biology, omics data, and computational tools. Key resources include databases such as DrugBank, TCMSP, PharmGKB, and tools like STRING, Cytoscape, and AutoDock. Case studies involving herbal medicines (e.g., Scopoletin, MXSGD, ZJC) illustrate the application of NP in cancer and viral disease treatment. NP enabled the identification of multi-target mechanisms, revealed key signaling and metabolic pathways, and validated compound–target interactions through molecular docking and biological assays. It also facilitated the repurposing of approved drugs and supported the scientific basis of traditional medicines. NP bridges traditional and modern drug discovery by offering a systems-level understanding of complex diseases and treatment mechanisms. It accelerates therapeutic development, enhances precision medicine, and supports the rational design of herbal-based multi-target therapies.